Fever following an Epidural Blood Patch in a Child - Agnes I. Hunyady; Corrie T. M. Anderson; John D. Kuratani; Anjana Kundu (Case Reports in Anesthesiology)
There is increasing evidence that children suffer from the consequences of spontaneous or iatrogenic intracranial hypotension. Pediatric epidural blood patch is gaining popularity because of its ability to alter cerebrospinal fluid dynamics and to alleviate headaches attributed to low cerebrospinal fluid pressure. There is, however, still not enough data to document the safety profile of an epidural blood patch. Here we describe a case of a fever in a child temporally related to the administration of an epidural blood patch. This case depicts the dilemmas in making the diagnosis and instituting treatment for complications of this procedure in the pediatric population.